Desain Pengembangan Media Pembelajaran Spin Microsoft PowerPoint Berbasis Literasi Asesmen Kompetensi Minimum (AKM) pada Materi Thaharah Sekolah Menengah Kejuruan - Vachruddin, Vrisko Putra; Assegaf, Abd. Rachman (Jurnal Penelitian Pendidikan Islam, 2021)
The development of learning media is very necessary because to avoid boredom levels and achieve learning goals effectively and efficiently, teachers must be innovative, creative and always varied in using learning media. One of the common and easy-to-use learning media is the power point media. The use of power points is generally monotonous and boring if filled with materials only. Media power point turned out to be developed into a spin game (spin) by filled with problems that are current trends, namely literacy and numeracy of minimum competency assessment (AKM). This research is included in research and development (R&D) research using the ADDIE model. The stages in this research are analysis, design, development, implementation, evaluation. The results showed that the product feasibility test through questionnaire assessment by learners showed a figure of 79% which is the category "Worthy". In addition, the evaluation results showed some of the advantages and disadvantages of AKM literacy-based spin PPT learning media.